Sugar-sweetened beverages, relative grip strength, and psychological symptoms among rural adolescents in western China: a cross-sectional study - Zhang, Yanni; Xiong, Jianping; Sun, Rong; Chai, Guangxin; Xiong, Li (Frontiers in Nutrition, 2025)
BackgroundThe increasing prevalence of psychological symptoms in adolescents has become an important problem faced by all countries in the world. The increased sugar-sweetened beverages (SSB) consumption and the decreased muscle strength had a serious negative impact on adolescent health. However, previous studies have mainly focused on adolescents in developed countries and fewer studies have been conducted in developing countries, especially in rural areas of western China. This study aims to explore the association of sugar-sweetened beverages consumption, and relative grip strength with psychological symptoms among rural adolescents in western China.MethodsIn this study, 11,018 adolescents aged 13–18 years from rural areas of Xinjiang and Tibet in western China were recruited using stratified randomized whole-cluster sampling in 2023. The participants were assessed for sugar-sweetened beverages consumption, relative grip strength, and psychological symptoms. Non-parametric tests, t-tests, logistic regression analyses, and ordered logistic regression analyses of generalized linear models were used to analyze the associations of sugar-sweetened beverage consumption and relative grip strength with psychological symptoms in adolescents.ResultsThe proportions of adolescents with sugar-sweetened beverages consumption of <1 times/week, 2–4 times/week, and >4 times/week in rural areas of western China were 34.6, 52.7, and 12.7%, respectively. The prevalence of adolescents’ emotional problems, behavioral problems, social adjustment difficulties, and psychological symptoms were 28.7, 27.0, 20.2, and 22.1%, respectively. The mean and standard deviation of grip strength among adolescents was assessed as (32.52 ± 10.13) kg and the relative grip strength was (0.60 ± 0.16) in rural areas of western China. Taking participants with sugar-sweetened beverages consumption <1 times/week group and relative grip strength at the fourth quartile as the reference, participants with SSB consumption >4 times/week and relative grip strength at the first quartile had the highest risk (OR = 2.77, 95% CI: 2.09–3.67, p < 0.001) of psychological symptoms.ConclusionElevated sugar-sweetened beverages consumption and decreased relative grip strength were associated with an increased prevalence of psychological symptoms. Prospective cohort studies are needed in the future to explore the causal relationships among SSB consumption, muscle strength, and psychological symptoms.